Il principio del mutuo riconoscimento nell'ordinamento dell'Unione europea - Giorgi, Eloisa (Premio Ricerca «Città di Firenze», 2020)
The essay analyses the principle of mutual recognition as a legal technique of coordination of the Member States' legal systems. We examine its ability of ensuring effectiveness of the individual's fundamental rights and of favouring the European integration. The study of the principle is both static and dynamic. From a static standpoint, the analysis attempts to delineate the anatomy of mutual recognition, identifying its legal nature, its distinctive features in each of the three areas of its implementation (internal market, judicial cooperation in civil and criminal matters) and the variable geometry that characterises its application. From a dynamic point of view, the research examines the principle of mutual recognition as a technique for coordinating the legal systems of the Member States, in both its horizontal and vertical dimension.